2015
DOI: 10.1093/mnras/stv2239
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the super-Earth 55 Cnc e

Abstract: Considerable progress has been made in recent years in observations of atmospheric signatures of giant exoplanets, but processes in rocky exoplanets remain largely unknown due to major challenges in observing small planets. Numerous efforts to observe spectra of superEarths, exoplanets with masses of 1-10 Earth masses, have thus far revealed only featureless spectra. In this paper we report a 4-σ detection of variability in the dayside thermal emission from the transiting super-Earth 55 Cancri e. Dedicated spa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
148
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(166 citation statements)
references
References 68 publications
16
148
2
Order By: Relevance
“…In February 2015, we requested 9.5 hr of Director's Discretionary Time (DDT) on the Spitzer Space Telescope to continuously monitor the 2σ transit window of the planet as derived from our analysis of the HARPS-N RVs. As demonstrated by the codetection and subsequent studies of the transits and occultations of 55 Cnc e (Demory et al 2011(Demory et al , 2015bGillon et al 2012) and the confirmation of the transiting nature of HD 97658 b (Van Grootel et al 2014), Spitzer is indeed a very powerful facility to search for and measure with high precision the transits of low-mass RV planets thanks to its trailing orbit that allows it to monitor the same star continuously for a complete transit window, and to its ultra-high photometric precision (a few dozens of ppm per time interval of 30 min for 55 Cnc). Our programme was approved by the Spitzer Science Center (SSC) Director under the ID 11180 (PI: M. Gillon), and the SSC managed to schedule it for 14 April 2015, a few days before the end of the current visibility window of the star.…”
Section: Spitzer Observationsmentioning
confidence: 86%
“…In February 2015, we requested 9.5 hr of Director's Discretionary Time (DDT) on the Spitzer Space Telescope to continuously monitor the 2σ transit window of the planet as derived from our analysis of the HARPS-N RVs. As demonstrated by the codetection and subsequent studies of the transits and occultations of 55 Cnc e (Demory et al 2011(Demory et al , 2015bGillon et al 2012) and the confirmation of the transiting nature of HD 97658 b (Van Grootel et al 2014), Spitzer is indeed a very powerful facility to search for and measure with high precision the transits of low-mass RV planets thanks to its trailing orbit that allows it to monitor the same star continuously for a complete transit window, and to its ultra-high photometric precision (a few dozens of ppm per time interval of 30 min for 55 Cnc). Our programme was approved by the Spitzer Science Center (SSC) Director under the ID 11180 (PI: M. Gillon), and the SSC managed to schedule it for 14 April 2015, a few days before the end of the current visibility window of the star.…”
Section: Spitzer Observationsmentioning
confidence: 86%
“…As we can see, the two models can be better distinguished at longer wavelengths. The average transit depth of 55 Cancri e at 4.5 mu obtained with Spitzer Space Telescope (Demory et al 2016) is also shown in light blue.…”
Section: Hcn As a Tracer Of High C/o Ratio Atmospheresmentioning
confidence: 90%
“…The eclipse depth of 131±28 ppm observed by Demory et al (2012) with Spitzer/IRAC at 4.5 μm converts to a brightness temperature of 2360±300 K. Also, repeated eclipse observations suggested a variability of the thermal emission from the dayside of the planet over time (Demory et al 2016). Table 1 summarizes the most recent parameters for 55 Cancri e. Given these parameters, Zeng & Sasselov (2014) have modeled the plausible structure of the interior and Hu & Seager (2014) have modeled the possible atmospheric compositions.…”
Section: Introductionmentioning
confidence: 99%
“…However, follow-up secondary eclipse, phase-curve, and transit measurements (Demory et al , 2016a(Demory et al , 2016bRidden-Harper et al 2016;Tsiaras et al 2016), in conjunction with theoretical models (Lammer et al 2013;Ito et al 2015;Kite et al 2016), point to the existence of an envelope.…”
Section: Cncementioning
confidence: 99%